2014
DOI: 10.1007/jhep01(2014)016
|View full text |Cite
|
Sign up to set email alerts
|

Higgs phenomenology in Type-I 2HDM with U(1) H Higgs gauge symmetry

Abstract: It is well known that generic two-Higgs-doublet models (2HDMs) suffer from potentially large Higgs-mediated flavor-changing neutral current (FCNC) problem, unless additional symmetries are imposed on the Higgs fields thereby respecting the Natural Flavor Conservation Criterion (NFC) by Glashow and Weinberg. A common way to respect the NFC is to impose Z 2 symmetry which is softly broken by a dim-2 operator. Another new way is to introduce local U(1) H Higgs flavor symmetry that distinguishes one Higgs doublet … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 79 publications
(108 reference statements)
0
50
0
Order By: Relevance
“…[14][15][16][17]. In the 2HDMs with U(1) H symmetry (denoted as 2HDM U(1) hereafter), two Higgs doublets are charged under new local U(1) H gauge symmetry, and they break both electroweak (EW) and U(1) H Higgs gauge symmetries.…”
Section: Jhep06(2015)034mentioning
confidence: 99%
See 4 more Smart Citations
“…[14][15][16][17]. In the 2HDMs with U(1) H symmetry (denoted as 2HDM U(1) hereafter), two Higgs doublets are charged under new local U(1) H gauge symmetry, and they break both electroweak (EW) and U(1) H Higgs gauge symmetries.…”
Section: Jhep06(2015)034mentioning
confidence: 99%
“…In fact, the present authors investigated the constraints in the type-I 2HDM U (1) in detail, and discussed the current status of the Type-I 2HDM U (1) in light of the recent LHC results on Higgs properties and provided the future prospects in ref. [14]. Also they constructed the inert 2HDM model with U(1) H gauge symmetry and showed that the light dark matter (DM) mass region below ∼ m W is widely open if the Z 2 symmetry is implemented into local U(1) H gauge symmetry, due to newly open annihilation channels of the DM pair into the extra U(1) H gauge boson(s): HH → Z H Z H , ZZ H , which are not present in the ordinary inert 2HDM with discrete Z 2 symmetry [18].…”
Section: Jhep06(2015)034mentioning
confidence: 99%
See 3 more Smart Citations